(untitled) (Вісник: Міжнародні відносини, 2020)
The article analyzes the possible impact of the circumstances established in international commercial arbitration awards (prejudice) on the position of the tax authority on the legality of the use of new taxes adopted in violation to the principle of tax stability, gives examples of case law. Violation of the principles of taxation leads to numerous tax disputes in Ukraine, in which the courts must adhere to a single approach to the obligation of taxpayers to make appropriate changes, adopted in violation to the principle of stability. International commercial arbitrations awards cannot be a prejudice to change existing practice of non-application of new taxes adopted in violation to the stability principle of taxation in favor of the tax authority.